Relationships among bacterial cell size, diversity, and taxonomy in rumen - Liu, Sijia; Zheng, Nan; Wang, Jiaqi; Zhao, Shengguo (Frontiers in Microbiology, 2024)
The rumen microbial community plays a crucial role in the digestion and metabolic processes of ruminants. Although sequencing-based studies have helped reveal the diversity and functions of bacteria in the rumen, their physiological and biochemical characteristics as well as their dynamic regulation along the digestion process in the rumen remain poorly understood, which requires pure culture to demystify. Bacteria exhibit morphological differentiation associated with different species. Based on the difference in size or shape of microorganisms, size fractionation by filters with various pore sizes can be used to separate them. In this study, we used polyvinylidene difluoride filters with 300, 120, 80, 40, 20, 8, 6, 2.1, and 0.6 µm pore sizes to successively passed bacteria suspensions through them for analysis of microbial population distribution using 16S rRNA gene sequences. We found that bacteria from the different pore sizes were clustered into four branches (> 120 µm, 40-120 µm, 6-20 µm and 20-40µm, < 0.6 µm), indicating that size fractionation had effects in enriching specific groups but could not effectively separate dominant groups by cell size alone. The species of unclassified Flavobacterium, unclassified Chryseobacterium, unclassified Delftia, Methylotenera mobilis, unclassified Caulobacteraceae, unclassified Oligella, unclassified Sphingomonas, unclassified Stenotrophomonas, unclassified Shuttleworthia, unclassified Sutterella, unclassified Alphaproteobacteria, unclassified SR1 can be efficient enriched or separated by size fractionation. In this study, we investigated the diversity of sorted bacteria populations in the rumen for preliminary investigations of the relationship between size and classification of rumen bacteria that have the potential to improve our ability to isolate and culture bacteria from the rumen in the future.